Consequences of Performance-Based Payments and Regulatory Schemes from the Perspective of Health Managers: A Qualitative Study - Saeid Karimi; Mahmood Nekoei Moghadam; Narges Hashemi; Mohammad Reza Tavakoli (Kerman University of Medical Sciences, 2022)
Introduction: The implementation of the performance-based payment scheme sparked a hope that the changes in the payment of financial rewards to employees in a fair manner and based on their performance can increase employees' motivation and job satisfaction. Accordingly, this study investigated the consequences of performance-based payments and regulatory schemes from the perspective of health managers in selected educational and medical centers in Isfahan.Methods: This qualitative study was conducted using a phenomenological approach. The data in this study were collected through in-depth interviews with eleven experts working in the management divisions of hospitals and central offices as well as the staff and faculty members of Isfahan University of Medical Sciences. The respondents were selected using purposive sampling. The collected data were analyzed using the content analysis method.Results: The consequences of performance-based payments were explained by one main theme (the consequences of implementing the performance-based payment plan in the health system) and four subthemes. Besides, one main theme (the general national and professional factors of the health system affecting the regulatory schemes) and five subthemes accounted for regulatory schemes.Conclusion: Payment regulatory schemes should be formulated effectively to address the problems associated with the current payment system so that the establishment of a performance-based payment system can serve as a mechanism to achieve this goal and a basis for reforming the existing payment systems.